Answer:
a = -87/13
b = 41/13
Explanation:
3a + 7b = 2
2a + 9b = 15
You need to have one of the coefficients have the same number but the opposite sign in both equations. Multiply the first equation by -2 and the second equation by 3. You will then be able to cancel out a and solve for b.
-2(3a + 7b) = -2(2)
-6a - 14b = -4
3(2a + 9b) = 3(15)
6a + 27b = 45
-6a - 14b = -4
6a + 27b = 45
0a + 13b = 41
13b = 41
b = 41/13
Plug in the b-value into one of the given equations and solve for a.
3a + 7b = 2
3a + 7(41/13) = 2
3a + 287/13 = 2
3a = -261/13
a = -87/13